Reactive oxygen species affect spinal cell type-specific synaptic plasticity in a model of neuropathic pain - Bittar, Alice (Pain, 2017)
Spinal synaptic plasticity is believed to drive central sensitization that underlies the persistent nature of neuropathic pain. Our recent data showed that synaptic plasticity in the dorsal horn is cell type-specific: intense afferent stimulation produced long-term potentiation (LTP) in excitatory spinothalamic tract neurons (STTn), whereas it produced long-term depression (LTD) in inhibitory GABAergic interneurons (GABAn). In addition, reactive oxygen species (ROS) were shown to be involved in LTP in STTn (STTn-LTP) as well as in LTD in GABAn (GABAn-LTD). This study examined the roles of two biologically important ROS—superoxide [·O(2)] and hydroxyl radicals [·OH]—in neuropathic mechanical hyperalgesia and cell type-specific spinal synaptic plasticity. A [·O(2)] donor induced stronger mechanical hyperalgesia than a [·OH] donor in naïve mice. A [·O(2)] scavenger showed greater anti-hyperalgesic effect than [·OH] scavengers in the spinal nerve ligation (SNL) mouse model of neuropathic pain. Moreover, a [·O(2)] donor induced STTn-LTP and GABAn-LTD, but a [·OH] donor induced only GABAn-LTD. In addition, a [·O(2)] scavenger inhibited STTn-LTP and GABAn-LTD induction (via conditioning stimulus (CS)) in naïve mice and alleviated SNL-induced potentiation and depression, respectively. Also, [·OH] scavenger selectively inhibited GABAn-LTD induction and maintenance as well as SNL-induced depression. These results indicate that mechanical hyperalgesia in SNL mice is the result of the combination of STTn-LTP and GABAn-LTD. Behavioral outcomes compliment electrophysiological results which suggest that [·O(2)] mediates both STTn-LTP and GABAn-LTD, whereas [·OH] is involved primarily in GABAn-LTD.